COMPARATIVE ANALYSIS OF SYARIAH BANK IN INDONESIA - , La Ode Anhusadar, Husain Insawan, Muljibir Rahman (International Journal of Advanced Science and Technology, 2020)
This study aims (1). to find out and analyze the efficiency data of Islamic banking in Indonesia Data Envelopment Analysis (DEA) with input-output variables that the author uses (2). To find out the causes of inefficiencies in the classification of Islamic banking financial operations in Indonesia during the period 2013 - 2017 (3). To find out the factors that influence the efficiency of Islamic banking in Indonesia. This type of research conducted in this study is quantitative research with non-parametric and parametric approaches. The non-parametric approach uses the Data Envelopment Analysis (DEA) method to measure the efficiency of the Decision-Making Unit (UPK), then the parametric approach to find out what factors influence the efficiency using the Tobit Regression method. Samples selected were 11 Islamic banks, namely: Syariah Bank Mandiri, BRI Syariah, Muamalat Indonesia, BNI Syariah, Victoria Syariah, BCA Syariah, Dubai Syariah Panin, BTPN Syariah, Maybank Syariah, Aceh Syariah banks and Bukopin Syariah. The conclusions of this study are (1). The management of financial operations at Islamic Banks in Indonesia during the 2013-2017 period was significantly inefficient. This happened because 54 DMUs used in this study only contained 34 DMUs or 63% achieved CRS efficiency and 48 DMUs or 89% achieved VRS efficiency, (2). Of the 11 Islamic banks studied, there were only two Islamic banks that achieved CRS and VRS efficiency, namely PT Bank BRI Syariah and PT Bank Aceh Syariah from 2013 to 2017, (3). Based on the results of the study it can be concluded that the inefficient DMU in the management of financial operations during the period of 2013 to 2017 in the CRS reached 20 DMU while in VRS 6 DMU.